KEPEMIMPINAN TRANSFORMASIONAL DALAM PENDIDIKAN ABAD 21: KAJIAN LITERATUR - Sidabutar, Yanti Arasi; Yusnadi; Asih Menanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of transformational leadership in addressing the challenges of 21st-century education through a literature study approach. Twenty-first-century education is characterized by technological development, globalization, and changing societal needs that require educational institutions to adapt innovatively and effectively. The research method used is qualitative research with a literature study design. Data were obtained from various scientific sources such as journals, books, articles, and academic documents related to transformational leadership and 21st-century education. Data collection techniques were conducted through documentation studies, while data analysis used content analysis techniques. The findings indicate that transformational leadership plays an important role in improving educational quality through motivation, inspiration, innovation, and individual potential development. The characteristics of transformational leadership, such as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, contribute to improving teacher performance, learning innovation, collaborative culture, and technological adaptation in education. In addition, transformational leadership also supports the development of 21st-century student competencies, such as critical thinking, creativity, communication, and collaboration. Therefore, transformational leadership is considered a relevant and effective leadership approach in facing the dynamics of modern education.